Solution-processable silicon naphthalocyanine tetraimides as near infrared electron acceptors in organic solar cells. (January 2022) - Cai, Chunsheng; Wang, Lei; Hu, Ming; Li, Li; Fu, Jubiao; Zhao, Xiaohong; Zhang, Youdi; Hu, Yu; Yuan, Zhongyi
Abstract: Two silicon naphthalocyanine electron acceptors, CH3 O-SiNcTI and 3BSO-SiNcTI, with four strong electron-withdrawing imide groups, were designed, synthesized, and applied in bulk heterojunction organic solar cells (BHJ OSCs). They exhibited strong near-infrared absorption in 300–1100 nm, maximum extinction coefficients of up to 5.2 × 10 5  M −1  cm −1, deep lowest unoccupied molecular orbital energy levels of −3.92 eV, and good photothermal stability. The power conversion efficiency of BHJ OSCs based on acceptor of 3BSO-SiNcTI reached 4.22%, which is the highest value among solution-processable phthalocyanine or naphthalocyanine derivatives. The measurements of space-charge-limited current, charge recombination, charge collection capability, atomic force microscopy (AFM), and transmission electron microscopy (TEM) were carried out. It is found that BHJ OSCs based on PTB7-Th:3BSO-SiNcTI, have higher and balanced carrier mobility, less charge recombination, better charge transport, and favorable film morphology, which lead to their higher photovoltaic performance. This study indicates the great potential of SiNcTIs as near-infrared chromophores for high-performance electron acceptors in BHJ OSCs. Graphical abstract: Image 1 Highlights: Soluble silicon naphthalocyanine tetraimides (SiNcTIs) as electron acceptors were designed and synthesized. SiNcTIs with intense NIR absorption, excellent stability, suitable energy levels, and well solubility are potential acceptors. The PCE of the bulk heterojunction organic solar cell based on acceptor 3BOS-SiNcTI reached 4.22%.